FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN RUPTUR PERINEUM PADA IBU BERSALIN DI RSIA P CIPONDOH KOTA TANGERANG TAHUN 2024 - Widi Sagita; Septiana Dian Widya Wati (Politeknik Karya Husada, 2025)
Abstract Background: Perineal rupture occurs in almost all first deliveries and not infrequently in subsequent deliveries. Perineal rupture is influenced by several factors, namely parity, education, occupation and newborn weight. Research objective: to determine the factors associated with the incidence of perineal rupture in mothers giving birth at RSIA P Cipondoh, Tangerang City in 2024. Research method: quantitative analytic with a cross-sectional design. The sample in the study of mothers giving birth who experienced perineal rupture at RSIA P Cipondoh, Tangerang City in January-June 2025 was 103 people with a total sampling technique. The data used is secondary data, then analyzed using the chi-square test. Research Results: The results obtained in the study are variables related to the incidence of perineal rupture, namely parity with a P Value (0.000) and OR 6.288 (2.416-16.353), education with a P Value (0.001) and OR 5.527 (2.128-14.353), occupation with a P Value (0.000) and OR 8.182 (2.603-25.717), and finally the variable of newborn weight with a P Value (0.000) and OR 10,000 (3.875-25.810). Conclusion: In this study, all variables studied, namely parity, education, occupation, and newborn weight, are related to the incidence of perineal rupture in mothers giving birth. Suggestion: Midwives are expected to minimize the occurrence of perineal rupture in mothers giving birth by establishing cooperation from pregnancy to the delivery process. Keywords: Perineal Rupture, Maternity Mother